Development and validation of a scoring system for advanced colorectal neoplasm in young Korean subjects less than age 50 years - Kim, Ji Yeon; Choi, Sungkyoung; Park, Taesung; Kim, Seul Ki; Jung, Yoon Suk; Park, Jung Ho; Kim, Hong Joo; Cho, Yong Kyun; Sohn, Chong Il; Jeon, Woo Kyu; Kim, Byung Ik; Choi, Kyu Yong; et al. (Intestinal research, 2019)
Colorectal cancer incidence among patients aged ≤50 years is increasing. This study aimed to develop and validate an advanced colorectal neoplasm (ACRN) screening model for young adults aged <50 years in Korea. This retrospective cross-sectional study included 59,575 consecutive asymptomatic Koreans who underwent screening colonoscopy between 2003 and 2012 at a single comprehensive health care center. Young Adult Colorectal Screening (YCS) score was developed as an optimized risk stratification model for ACRN using multivariate analysis and was internally validated. The predictive power and diagnostic performance of YCS score was compared with those of Asia-Pacific Colorectal Screening (APCS) and Korean Colorectal Screening (KCS) scores. 41,702 and 17,873 subjects were randomly allocated into the derivation and validation cohorts, respectively, by examination year. ACRN prevalence was 0.9% in both cohorts. YCS score comprised sex, age, alcohol, smoking, obesity, glucose metabolism abnormality, and family history of CRC, with score ranges of 0 to 10. In the validation cohort, ACRN prevalence was 0.6% in the low-risk tier (score, 0-4), 1.5% in the moderate-risk tier (score, 5-7), and 3.4% in the high-risk tier (score, 8-10). ACRN risk increased 2.5-fold (95%CI, 1.8-3.4) in the moderate-risk tier and 5.8-fold (95%CI, 3.4-9.8) in the high-risk tier compared with the low-risk tier. YCS score identified better balanced accuracy (53.9%) than APCS (51.5%) and KCS (50.7%) scores and had relatively good discriminative power (area under the curve=0.660). YCS score based on clinical and laboratory risk factors was clinically effective and beneficial for predicting ACRN risk and targeting screening colonoscopy in adults aged <50 years.